Menjadi Pembawa Acara yang Profesional: Memahami Peran, Teknik, dan Strategi Sukses dalam Berbagai Konteks Acara - Nailatur Rizqiyah; Masti Yanto; Mad Sa’i (INDO PUBLISHING, 2025)
Currently, the profession of a presenter is increasingly in demand by many people. To become a professional presenter, theoretical and practical knowledge of this profession is required. So this article aims to explain how a presenter can achieve a high level of professionalism. This research method is a descriptive analytical library research. The procedure for obtaining the data is carried out through document analysis. Document analysis is carried out by studying literature in the form of books and journal articles related to the material discussed in this article. It can be concluded that a presenter has a very crucial role in an event, where he plays a role in guiding the event from beginning to end. The basic techniques that must be mastered by a presenter include: mastery of language and articulation, control of emotions and body gestures, interaction with the audience, and preparation of materials and improvisation. The strategies that can be applied to become a presenter in order to be able to become a successful presenter in every event include: knowing the event and audience, preparing yourself thoroughly, practicing public speaking skills, building chemistry with the audience, controlling time well, self-evaluation after the event. A presenter must understand the role, techniques and strategies of being a presenter so that he/she can be a professional presenter.